Optimization Condition Of Bio-Process For Phenol Degradation In Oil Refinery Wastewater - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACT Erni Martani , Sri Astuti Rahayu, Bardi Murachmaniand Noegroho Hadi Hs. 2000 â Optimization condition of bio-process for phenol degradation in oil refinery wastewater. Biologi 2(10): 553-565 Imperfect bio-process of oil refinery wastewater will cause environmental pollution due to the high concentration of phenol and ammonia. Therefore, this study was done to investigate possible alternatives in improving the bio-processing unit. The oil refinery wastewater sample was taken from inlet of wastewater treatment of an oil industry in West Java. Several treatments in bio-process were conducted by adjusting aeration flow rate, N/P ratio (by urea addition), bacterial inoculation, and their variation. An optimal condition for bio-process was based especially on the phenol degradation. Ammonia content and the COD level during incubation period were analyzed as supporting data. Chemical analyses of the wastewater sample showed that BOD, COD, phenol and ammonia concentration were higher than allowed concentration in oil refinery wastewater. Microbial examination indicated that Pseadomonas and Bacillus were dominating the wastewater. Therefore, they were chosen as bacterial inoculants. The experiments showed that phenol degradation wa.t.enhanced by aeration, and it was greatest at flow rate of 201/min. Complete phenol degradation was observed in this flow rate within 48 hours. This optimal flow rate was used in combination treatment with nutrition addition and bacterial inoculation. Based on phenol degradation, single aeration treatment at 201/min was the best compared to other treatments. However, com plete phenol degradation was not always followed by COD and ammonia reduction. Studies are still required to get a better quality of wastewater based on several environmental quality parameters.